2023
DOI: 10.1039/d3ta03911k
|View full text |Cite
|
Sign up to set email alerts
|

Hemi-methylamine lithium borohydride as electrolyte for all-solid-state batteries

Abstract: Utilization of next-generation all-solid-state lithium batteries require new fast Li-ion conducting solid electrolytes. LiBH4-based materials have emerged as a promising class of Li+-conductors, and recent advancements show sufficiently high ionic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…Thus, many structural tuning approaches, such as anion substitution, neutral-molecule incorporation, and nanoconfinement, have been developed to improve the ionic conductivity of their low-temperature phases or lower the order–disorder transition temperature. The neutral-molecule incorporation approach is mainly based on the intermolecular interaction between neutral molecules (e.g., NH 3 , CH 3 NH 2 , NH 3 B 3 H 7 , NH 2 CH 2 CH 2 NH 2 , or NH 3 BH 3 ) and hydridoborates (e.g., LiBH 4 , Mg­(BH 4 ) 2 or KB 3 H 8 ). , In these cases, a solid solution of hydridoborates and the neutral-molecule formed, which either stabilizes massive mobile cations by a network of dihydrogen bonds between protonic H of the neutral molecule and hydridic H of hydridoborate anion or leads to a lower melting temperature. Our previous data showed that the neutral-molecule incorporation approach also had applicability to improve the ionic conductivity of KB 3 H 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many structural tuning approaches, such as anion substitution, neutral-molecule incorporation, and nanoconfinement, have been developed to improve the ionic conductivity of their low-temperature phases or lower the order–disorder transition temperature. The neutral-molecule incorporation approach is mainly based on the intermolecular interaction between neutral molecules (e.g., NH 3 , CH 3 NH 2 , NH 3 B 3 H 7 , NH 2 CH 2 CH 2 NH 2 , or NH 3 BH 3 ) and hydridoborates (e.g., LiBH 4 , Mg­(BH 4 ) 2 or KB 3 H 8 ). , In these cases, a solid solution of hydridoborates and the neutral-molecule formed, which either stabilizes massive mobile cations by a network of dihydrogen bonds between protonic H of the neutral molecule and hydridic H of hydridoborate anion or leads to a lower melting temperature. Our previous data showed that the neutral-molecule incorporation approach also had applicability to improve the ionic conductivity of KB 3 H 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Metal borohydrides are a fascinating and continuously expanding class of materials, and their extremely rich chemistry, including a wide range of compositions and structural flexibility, has resulted in a plethora of new materials in the past decade. These new materials exhibit a wide variety of interesting properties such as luminescence, magnetism, semiconductivity, and superionic conductivity. The interest in metal borohydrides as superionic conductors was initiated by the discovery of fast Li + conductivity in the high-temperature polymorph of LiBH 4 in 2007 . Since then, there have been numerous reports on strategies to improve the ionic conductivity at lower temperatures, often by cation or anion substitution, nanostructuring, or nanocomposite formation. , More recently, metal borohydride derivatives with neutral ligands, such as LiBH 4 coordinated with different neutral molecules (H 2 O, NH 3 , CH 3 NH 2 , and NH 3 BH 3 ), have received increased attention and have demonstrated the highest reported ionic conductivities among LiBH 4 -based conductors. Likewise, this strategy has also proven fruitful for multivalent (e.g., Mg 2+ ) ionic conductors, and the highest solid-state Mg 2+ conductivities are reported for Mg­(BH 4 ) 2 derivatives with neutral ligands such as NH 3 , CH 3 NH 2 , NH 3 BH 3 , (CH 3 ) 2 CHNH 2 , NH 2 CH 2 CH 2 NH 2 , and O­(CH 2 ) 4 . The underlying mechanism behind this new type of ionic conductors is still not completely understood, but the flexible structural framework and versatile coordination of BH 4 – appear to be crucial, and an exchange of the neutral molecule between framework and interstitial cations may promote the cationic conductivity. ,, Dynamic studies on other related materials have shown that BH 4 – may actively promote the ionic conductivity through rapid reorientations as reported for the LiLa­(BH 4 ) 3 X (X = Cl, Br, I) and LiBH 4 –LiI systems. Likewise, rapid BH 4 – dynamics were also identified in the fast Li + ion conductor LiBH 4 ·NH 3 . , Thus, the dynamics of BH 4 – play an important role for physical properties such as high cation conductivity . A related class of materials with larger boron–hydrogen cluster anions are also receiving significant attention, where the rapid reorientation of the polyhedral anions in M 2 B x H x and MCB x –1 H x (M = Li, Na, and K; x = 10 and 12) plays an important part in the superionic conductivities observed in these systems …”
Section: Introductionmentioning
confidence: 99%
“…Borohydride-based SSEs, a subtype of hydride electrolytes, represented by LiBH 4 -LiCl-P 2 S 5 composites, exhibit enhanced Li-ion conduction under nanoconfinement and demonstrate favorable wetting properties. Nevertheless, they grapple with the issue of hydrogen embrittlement and high reactivity [8]. Halide solid-state electrolytes are intensively studied for application in ASSB due to their favorable combination of high ionic conductivity and chemical and electrochemical stability.…”
Section: Introductionmentioning
confidence: 99%